Strengthening of Local Micro Business Legal (UMKM) Law Regulation in Requiring Sustainable Tourism in Bali - I Ketut Gde Suarnatha; Ida Bagus Wyasa Putra (Fakultas Hukum, Universitas Warmadewa, 2020)
Sociological study of local MSMEs in facing various obstacles in their growth and development and juridical studies related to the legal basis underlying the need to strengthen the competitiveness of local MSMEs in Bali. This research aims to analyze the factors that affect the competitiveness of local micro, small and medium enterprises (MSMEs) in organizing the trade in tourism services in Bali. This research used is normative research method. This research uses several approaches including: conceptual approach, philosophical approach and analytical approach. The results of this study showed that the formulation of strengthening the competitiveness of local micro, small and medium enterprises (MSMEs) in organizing the tourism services trade in Bali is based on the principle of fair efficiency and the principle of subsidarity so that local MSMEs can become new entities that reflect the philosophy of Tri Hita Karana and have strong competitiveness realize sustainable tourism. It is recommended to the Provincial Government of Bali, to make efforts to crystallize the value of local wisdom that can be applied as the identity of local MSMEs, so that there are formal standards in determining local MSMEs as a new entity in the economic world.